Assessment of Sleep Disturbance in Patients with Primary and Secondary Glossodynia - Abe Susumu; Momota Yukihiro; Matsuka Yoshizo; Ohkawa Toshinori; Horikawa Eriko; Hayama Rika; Okura Kazuo; Kawano Fumiaki (Japanese Journal of Orofacial Pain, 2017)
Purpose: Although chronic pain might affect to sleep, there is no clearly defined relation between orofacial pain and sleep. The aim of this study was to illustrate the quality of sleep for the patients with glossodynia as oral chronic pain using sleep questionnaire.Methods: Thirteen primary glossodynia and nineteen secondary glossodynia patients were compared with nineteen healthy control subjects （HC） matched for age and sex. Especially, secondary glossodynia was decided as oral candida disease. The Japanese version of Pittsburgh sleep quality index （PSQI） and the visual analog scale （VAS） for glossalgia were administrated. The evaluated items contained the seven sleep-related components, PSQI global score （PSQIG）, illness duration and VAS for sleep disturbance. Furthermore, PSQIG was divided into sleep disturbance or non-sleep disturbance to indicate quality of sleep.Results: There were not significant differences between sleep conditions and illness duration or VAS in glossodynia patients in comparison with HC. However, primary glossodynia patients had higher score of subjective sleep quality than HC （P＝0.03）. Secondary glossodynia patients had higher scores of subjective sleep quality than HC （P＝0.02, respectively）. Furthermore, sleep disturbance of each glossodynia patients was significant worse than HC （P＝0.04）.Conclusion: Glossodynia patients complained sleep disturbance as compared with healthy control subjects. Glossalgia as oral chronic pain might reduce quality of sleep. 目的：慢性痛は睡眠に影響を及ぼすと考えられているが，口腔顔面痛と睡眠との関係は明確ではない．本研究では慢性的な口腔顔面痛として舌痛症患者の睡眠状態を検討することを目的とした．方法：舌痛症患者群は2012年6月から2015年12月の間に徳島大学病院を来院し，一次性舌痛症と診断された患者（13名；男性1名，女性12名）と，培養検査で口腔内にカンジダの存在が確認された二次性舌痛症患者（14名；男性3名，女性11名）である．対照群として補綴治療希望患者のうち，全身状態が良好で口腔粘膜に痛みを伴わない者（14名；男性2名，女性12名）を抽出した．年齢・男女比は患者群と同じ構成になるように抽出した．質問表はピッツバーグ睡眠質問表日本語版（PSQI-J）を用いた．睡眠の質や睡眠障害は睡眠関連項目7要素とPSQI global score （PSQIG）で評価した．結果：一次性と二次性舌痛症患者の受診までの病悩期間に有意差はなく，痛み強度も有意差を認めなかった．一方，全舌痛症患者の睡眠の質は対照群よりも低下していた．一次性，二次性舌痛症患者ともに対照群に比べて睡眠の質が有意に低下していた（P＝0.03，P＝0.02）．また，二次性舌痛症患者では対照群に比べて，睡眠障害を示すPSQIGにおいて有意な増加を認めた（P＝0.04）．結論：慢性的な口腔顔面痛である舌痛症患者は睡眠の質が対照群に比べて良くなく，睡眠障害があることが示された．